Residential segregation and social exclusion in Brazilian housing markets - Maria da Piedade Morais; Bruno de Oliveira Cruz; Carlos Wagner de Albuquerque Oliveira (Institute for Applied Economic Research (ipea), 2015)
This paper seeks to analyze the set of characteristics that can explain the existence of slums (favelas) in Brazilian cities, based upon microdata from the 1999 edition of the National Household Survey (Pnad), published by the Brazilian Institute of Geography and Statistics (IBGE). The paper is divided in 2 main parts. In the first part, we make a brief description of the urbanization trends, the process of slum formation and the poverty profile in Brazil and present a survey of the empirical literature on social exclusion and spatial segregation. The second part of the article describes a logit regression designed to test the hypothesis if local, regional and personal attributes such as immigration, income level, household size, schooling, tenure conditions, gender, race, age, labor market insertion, sector of activity, city size and other locational variables are important to explain the existence of slums and residential segregation in the housing markets of the major Brazilian cities. Other concern of the paper is the nature of the relationship established between labor and housing markets, and the way in which discrimination and segmentation in both markets reinforce each other. By shedding some light on the causes and the nature of social discrimination and spatial segregation faced by slum-dwellers in Brazil (favelados), this study can aid policy makers to design more efficient urban and regional development policies in order to fight urban poverty in Brazil and in other developing countries.
Keywords: 330